ANALYSIS OF THE INFLUENCE OF NATURAL GAS COMPRESSIBILITY FACTOR DETERMINATION METHODS ON THE VOLUME OF PRODUCTION AND TECHNOLOGICAL GAS LOSSES IN THE GAS TRANSMISSION SYSTEM - Drin , N. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2025)
The article presents a comparative analysis of the current Ukrainian regulatory methodologies (based on SOU/NDTOV) and the international reference standard (ISO 20765-1/AGA8) for determining the volume of production and technological gas losses (PTL) that occur during planned maintenance operations on main gas pipelines. The critical influence of the gas compressibility factor (Z) on the accuracy of the final calculated PTL volume is investigated. The relevance of the study is dictated by the exceptional strategic importance of the Ukrainian Gas Transmission System (GTS). Given the unstable loading and high wear of the infrastructure, the regular execution of planned preventative maintenance (PPM) is an indispensable condition for ensuring reliability. Every such operation involves technological gas losses, the volume of which, according to regulations, is determined by calculation. The accuracy of these calculations directly affects the formation of the fuel and energy balance of the GTS Operator. Underestimation or overestimation of PTL volumes leads to financial risks and distortion of performance data regarding operational efficiency. Particular attention is paid to the gas compressibility factor (Z), which is a key parameter for converting gas volumes from operating conditions to standard conditions. The use of simplified formulas, which do not account for the full chemical composition of the gas, creates a systematic error. Minimizing this error is a direct pathway to enhancing market transparency and energy efficiency. In the context of European integration processes, the alignment of national calculation methodologies with international standards becomes a matter of primary importance. Thus, ensuring maximum accuracy in PTL accounting is a critical task for the financial sustainability and technical reliability of the Ukrainian GTS. Based on hypothetical initial data for a typical section of a main gas pipeline, it is demonstrated that the application of the simplified methodology (Method 2) leads to systematic gas under-accounting, as its calculated coefficient significantly differs from the reference one.